Early childhood fundamental motor skills: visual impairments and non-visually impaired - Widyawan, Dena (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this study was to test fundamental motor skills (FMS) in young children with visual impairments (VI) and non-VI children. This study used a cross-sectional design, descriptive-analytic with purposive sampling. Children without VI showed higher locomotor skills (M= 21.38, SD= 6.69) when compared to children with VI (M= 9.70, SD= 3.09). Children without VI showed higher ball skills (M = 18.74, SD = 6.54) when compared to children with VI (M = 5.23, SD = 5.44)). For locomotor skills there was a significant effect on vision (F=17.55, p=.014, η2=.31). For children with VI, birth control (n=7) performed higher (M=10.33, SD=10.54) compared to non-birth VI (n=3; M 4.02, SD=2, 73). For ball skills there was a significant effect on vision (F=21.99, p<0.001, η2=.56). For children with VI, congenital VI (n=7) performed higher (M=6.73, SD=6.69) than non-congenital blind (n=3; M=2.05, SD=1.01). Non-blind children show higher levels of FMS when compared to children with VI. The children with VI in this sample exhibited profound developmental delays requiring further investigation and future intervention.